Genetic variation of the second exon of ELA-DRB genes in Argentine Creole horses - Diaz, Silvina (2008)
Genetic variation in the equine leucocyte antigen-DRB (ELA-DRB) second exon was investigated using polymerase chain reaction (PCR) amplification, restriction fragment length polymorphism (RFLP) of PCR products (PCR-RFLP) and deoxyribonucleic acid (DNA) sequencing. Eight distinct PCR-RFLP patterns could be identified in the studied Argentine Creole (AC) horses. The number of observed patterns per individual ranged from four to six, thus confirming the presence of multiple DRB copies in AC horses. Three PCR-RFLP alleles and three new sequences were identified. The estimated rates of synonymous and non-synonymous substitutions among ELA-DRB exon 2 sequences were higher within the antigen recognition site (ABS) than on the non-ABS. Phylogenetic analysis showed that the nucleotide sequences clustered in two main groups, while some sequences were not included in either group. Finally, the identification of the number of alleles per animal, the phylogenetic and segregation analyses allowed us to explain the number of ELA-DRB loci. However, it was not possible to identify specific alleles with specific loci.